AIR-SIDE PERFORMANCE OF A MICRO-CHANNEL HEAT EXCHANGER IN WET SURFACE CONDITIONS - Srisomba, Raviwat; Asirvatham, Lazarus Godson; Mahian, Omid; Dalkilic, Ahmet Selim; Awad, Mohamed M.; Wongwises, Somchai (VINCA INST NUCLEAR SCI, 2017)
The effects of operating conditions on the air-side heat transfer, and pressure drop of a micro-channel heat exchanger under wet surface conditions were studied experimentally. The test section was an aluminum micro-channel heat exchanger, consisting of a multi-louvered fin and multi-port mini-channels. Experiments were conducted to study the effects of inlet relative humidity, air frontal velocity, air inlet temperature, and refrigerant temperature on air-side performance. The experimental data were analyzed using the mean enthalpy difference method. The test run was performed at relative air humidity's ranging between 45% and 80%; air inlet temperature ranges of 27, 30, and 33 degrees C, refrigerant-saturated temperatures ranging from 18 to 22 degrees C, and Reynolds numbers between 128 and 166. The results show that the inlet relative humidity, air inlet temperature, and the refrigerant temperature had significant effects on heat transfer performance and air-side pressure drop. The heat transfer coefficient and pressure drop for the micro-channel heat exchanger under wet surface conditions are proposed in terms of the Colburn factor and Fanning factor.
Keywords: automotive air-conditioning; heat transfer coefficient; micro-channel heat exchanger; pressure drop; R-134a; TUBE; PUMP; Thermodynamics